Kicking & dreaming ebook A story of heart, soul, and rock & roll. - Wilson, Ann (2024)
The story of Heart is a story of heart and soul and rock ’n’ roll. Since finding their love of music and performing as teenagers in Seattle, Washington, Ann Wilson and Nancy Wilson, have been part of the American rock music landscape. From 70s classics like “Magic Man” and “Barracuda” to chart- topping 80s ballads like “Alone,” and all the way up to 2012, when they will release their latest studio album, Fanatic, Heart has been thrilling their fans and producing hit after hit. In Kicking and Dreaming , the Wilsons recount their story as two sisters who have a shared over three decades on the stage, as songwriters, as musicians, and as the leaders of one of our most beloved rock bands. An intimate, honest, and a uniquely female take on the rock and roll life, readers of bestselling music memoirs like Life by Keith Richards and Steven Tyler’s Does the Noise in My Head Bother You? will love this quintessential music story finally told from a female perspective.